Crisis in Syria and Turkish regional policy - Aktaulova, B.; Baigozhayeva, N. (Journal of Oriental Studies, 2016)
In this article was made an attempt to analyze and defi ne the main factors which led to crisis in Syria in terms of Turkish regional policy her neighbor country.